Pengaruh Harga dan Promosi terhadap Volume Penjualan pada UMKM Teh di Ngargoyoso Jawa Tengah - Mita, I Desak Nyoman; Gede Sadiartha, Anak Agung Ngurah; Wina Premayani, Ni Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The cause of this examine become to decide the impact of charge and advertising collectively on income extent at UMKM The Di Ngargoyoso, Central Java. In this examine the authors used a quantitative approach. This studies become carried out on Tea SMEs. in Ngargoyoso Village, Central Java. The trouble that takes place is that the profits of MSMEs in Sumbersari Village in Ngargoyoso District, Karanganyar Regency has increased, however, the promoting charge has a tendency now no longer to differ in order that the income extent of MSMEs for Tea. in Sumbersari Village in Ngargoyoso District, Karanganyar Regency become much less than optimal. The populace on this examine are customers of tea SMEs in Ngargoyoso, Central Java, whose quantity is infinite. The pattern technique used is chance sampling. In sampling, if the populace is infinite, then the pattern calculation makes use of the hair formula. The evaluation method used is a couple of regression evaluation. Based at the outcomes of the evaluation, it indicates that the charge variable has a high quality courting to income extent, the advertising variable has a high quality courting to income extent and the charge and advertising variables have a simultaneous impact on income extent.